TA'LIMDA TARIXIY-MADANIY MEROS VA O'QUVChILARNI MILLIY HUNARMANDChILIKKA O'RGATISh MASALALARI - Bekniyazov, B.S. (SCIENCE and SOCIETY, 2023)
This article discusses the issues of historical and cultural heritage in the education and training of schoolchildren in folk crafts, the use of historical and cultural heritage at school to instill in students a love for a particular profession, as well as the contribution of teachers to this activity.
Keywords: vocational guidance; craft; craftsman; crafts; national identity; national values; folk crafts; blacksmithing; jewelry; coppersmithing; wood carving; sewing; weaving; making various leather products; bone carving